Beyond interaction : tools and practices for situated publication in display networks - José, Rui (2012)
The ability to engage users in content generation is both a major goal and a major challenge for public displays. While previous work has extensively explored the specific challenges associated with interaction processes, little attention has been paid to the broad range of issues that go beyond interaction itself. More specifically, public display systems do not seem to offer a set of tools and techniques that people may feel comfortable to use for whatever communication purposes they might have. There are no publication concepts that can frame expectations on how content creation, distribution, presentation and curation are handled by display systems. In our research, we seek to explore new publication concepts for public displays, and for that purpose we have developed instant places, a platform enabling people to connect with the places they visit and control the projection of their identity in public displays. The system frames interaction events within two specific publication concepts: pin badges and posters. We describe our first deployments at three different locations and the results obtained from usage data and in-situ surveys about content publication practices.